2003
DOI: 10.1046/j.1365-2362.2003.01252.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of interleukin‐6, plasma viscosity, fibrinogen, von Willebrand factor, tissue factor and vascular endothelial growth factor levels in congestive heart failure

Abstract: IL-6 and TF are predictors of poor prognosis in chronic CHF, raising the hypothesis that IL-6 may contribute to the progression and thrombotic complications of CHF via its actions on TF expression. Although VEGF did not independently predict outcome in chronic CHF, the possibility arises that it may act with IL-6 to induce TF expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
1
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(57 citation statements)
references
References 45 publications
6
46
1
4
Order By: Relevance
“…Only point measurement could be another limitation of the study since repeated measures may be necessary to define the variance as well as the predictive nature of a biomarker [33], but in support of our findings, several studies previously reported the predictive value of only point measurement of inflammatory biomarkers in atrial fibrillation [34] and other clinical conditions such as congestive heart failure [35] acute myocardial infarction [36] and hypertension [37].…”
Section: Discussionsupporting
confidence: 79%
“…Only point measurement could be another limitation of the study since repeated measures may be necessary to define the variance as well as the predictive nature of a biomarker [33], but in support of our findings, several studies previously reported the predictive value of only point measurement of inflammatory biomarkers in atrial fibrillation [34] and other clinical conditions such as congestive heart failure [35] acute myocardial infarction [36] and hypertension [37].…”
Section: Discussionsupporting
confidence: 79%
“…Only point measurement could be a limitation of the study since repeated measures and a time course analysis of fetuin-A and CD40 L may be necessary to define the variance as well as the predictive nature of a biomarker [25], but in support of our findings several studies previously reported the predictive value of only point measurement of inflammatory biomarkers in atrial fibrillation [26] and other clinical conditions such as congestive heart failure [26] and acute myocardial infarction [27].…”
Section: Discussionsupporting
confidence: 77%
“…IL-1ß, also produced mainly by macrophages and the action of which overlaps partly with TNF, induces metalloproteinases, nitric oxide synthase, and adhesion molecules. Moreover, IL-6 and TNF-· have been proven to be clinical markers to identify and track inflammation (27)(28)(29)(30). Targeting inflammatory cytokines has been prosperously developed and been proven to successfully protect against atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%